Pengaruh Penerapan Model Inkuiri terhadap Hasil Belajar IPS di SD - azizah, azizah; Muhammadi, Muhammadi; Dalais, Mursal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study was aimed to determine the effects of the application of the Inquiry model on student learning outcomes in social studies learning class V at SDN Gugus I Kec. Canduang Kab. Agam in the even semester 2018/2019 academic year. This study was a quantitative research using True Experimental Design. The population of this study was fifth grade students of SDN Gugus I Kec. Canduang Kab. Agam. The sampling technique was Probability Sampling with Simple Random Sampling. The selected samples were class V SDN 14 V Suku Ateh and class V SDN 05 Suku Bawah, each of class consisted of 16 and 21 students.  Based on the conducted research, it was found that tcount>ttable is 6.09 >2.03 with α = 0.05, so it can be concluded that there were significant effects of applying the Inquiry model on student learning outcomes in social studies learning class V in SDN Gugus I  Kec. Canduang Kab. Agam. Keywords: Inquiry Model, Social Studies Learning, Learning Outcomes